PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PQ4R UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KOMPETENSI DASAR MENDESKRIPSIKAN PELAKU-PELAKU EKONOMI DALAM SISTEM PEREKONOMIAN INDONESIA KELAS VIII-A SMP NEGERI 2 MLANDINGAN - Ahmad Hafas Rasyidi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
Low activity and student learning outcomes can be caused by the experience of students working on social studies questions which they think are difficult, difficult and difficult because they do not understand a concept. The PQ4R cooperative learning model is used to help students remember what they read. With these reading skills, each student will enter a scientific world that is full of charm, understands the treasures that develop many other skills that are very useful for achieving success in life. Skilled reading activities will open up broad knowledge, gates to deep wisdom, and expertise in the future. In the implementation in cycle II, the results of student activity observations showed an increase. This can be seen in the activity of students who experienced a fairly high increase compared to the observations made in cycle I, namely there was an increase of 1.9%, namely 85.98% in the observation of student activity in cycle I to 87.88% although it was not too high an increase in learning activities, but This is sufficient to prove that the learning activities of class VIII-A students in social studies subjects are active. Student learning outcomes have met the standard of learning completeness ≥ 85% classical completeness, in cycle I there are 16 with a classical completeness percentage of 63.63% of students completing classically while in cycle II there is an increase in students who complete up to 20 children with a completeness percentage of 90, 91%.